Sistema de indicadores de sustentabilidade para o turismo: uma abordagem do artesanato de Antônio Prado - RS - Fantin, Carla (My University, 2018)
The search for sustainability has been a recurring theme in the field of tourism, due to its characteristics that generate influences in the locality in which it is developed. Therefore, the analysis of sustainability becomes a factor of significance, for the evaluation of the existing reality and for the promotion of actions, which aim at sustainable tourism. Thus, the present study aims to verify, through SISDtur, the economic, social and institutional sustainability of craftsmanship marketed in the house of Antônio Prado - RS artisan. For this, the methodology proposed by Hanai (2009), SISDTur, was used. The research is characterized as a unique case study, with descriptive nature and qualitative and quantitative approach. The data collection was done from the application of questionnaires, with closed questions about the craft and questions about the profile of the respondents. The main results showed that the commercialization of handicrafts in Antônio Prado - RS, is potentially sustainable, inferring that the activity has produced positive effects on the community involved, but, nevertheless, actions are necessary to guarantee its sustainability, since some indicators are unsustainable and partly unsustainable. In this way, it was possible to obtain the current panorama of the commercialization of handicrafts in Antônio Prado - RS, its positive and negative indicators, to assist in the construction of sustainable handicrafts in the locality.
A busca pela sustentabilidade tem sido tema recorrente no campo do turismo, devido as suas características que geram influências na localidade em que se desenvolve. Por isso, a análise da sustentabilidade torna-se fator de significância, para a avaliação da realidade existente e para a promoção de ações, que objetivem o turismo sustentável. Assim, o presente estudo tem por objetivo verificar, através do SISDtur, a sustentabilidade econômica, social e institucional, do artesanato comercializado na casa do artesão de Antônio Prado – RS. Para tanto, foi utilizada a metodologia proposta por Hanai (2009), o SISDTur. A pesquisa se caracteriza como um estudo de caso único, com natureza descritiva e enfoque qualitativo e quantitativo. A coleta de dados se deu a partir da aplicação de questionários, com questões fechadas sobre o artesanato e perguntas sobre o perfil dos respondentes. Os resultados principais evidenciaram que a comercialização do artesanato em Antônio Prado – RS, é potencialmente sustentável nos aspectos econômicos, sociais e institucional, inferindo que a atividade tem produzido efeitos positivos sobre a comunidade envolvida, mas, ainda assim, são necessárias ações para garantir sua sustentabilidade, já que alguns indicadores se apresentaram insustentáveis e parcialmente insustentáveis. Desta forma, foi possível obter o panorama atual da comercialização do artesanato em Antônio Prado – RS, seus indicadores positivos e negativos, para auxiliar na construção do artesanato sustentável na localidade.
Keywords: Turismo; Artesanato; Sustentabilidade; Tourism; Handicraft; Sustainability